The impact of EU legislation in the area of digital and green transition, particularly on SMEs: Study requested by the IMCO Committee - Julia Rzepecka; Aleksander Fuksiewicz; Francesca Squillante; Lukas Alijošius; Ilsa Godlovitch; Peter Stamm; Julia Wielgosch; Martin Lundborg (Publications Office of the European Union, 2024)
EU legislation calls SMEs to contribute to the twin transition. This study analyses the cumulative costs of selected pieces of EU digital and green legislation on SMEs and explores the effectiveness of costs mitigation tools at their disposal. This document was prepared for the Policy Department for Economic, Scientific and Quality of Life Policies at the request of the Committee on Internal Market and Consumer Protection (IMCO). – – Wie wirkt sich die EU Gesetzgebung hinsichtlich Digitalisierung und Klimaneutralität auf kleine und mittlere Unternehmen in der Praxis aus? Die EU-Gesetzgebung fordert die kleinen und mittleren Unternehmen (KMU) dazu auf, einen Beitrag zur doppelten Transformation, also zur Digitalisierung und Klimaneutralität zu leisten. Diese Studie von WIK-Consult und EY analysiert die kumulativen Kosten ausgewählter digitaler und grüner EU-Rechtsvorschriften für KMU und untersucht die Wirksamkeit der ihnen zur Verfügung stehenden Instrumente zur Kostenminderung. Die Studie wurde im Auftrag des Ausschusses für Binnenmarkt und Verbraucherschutz (IMCO) des Europäischen Parlaments für die politische Abteilung für Wirtschafts-, Wissenschafts- und Lebensqualitätspolitik erstellt.
Additional information: Study by WIK-Consult and EY for the European Parliament.
Keywords: 330